2017
DOI: 10.1177/0954411917690417
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of bicycle–car accidents under four different types of collision

Abstract: Bicycle riders are among the highest risk group in traffic. A cyclist simulation study captured kinematics and injuries to legs, pelvis, neck, and head for one human body size. We analyzed the number of parameters (forces acting on left and right tibia, head injury criterion, neck tensile force, neck shear force, and pelvic acceleration) for each of the four different cases: bicyclist ride out-residential driveway, motorist overtaking-undetected bicyclist, bicyclist left turn-same direction, and bicyclist righ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…It can be explained due to the different geometry between the fronts of the vehicles used because the cyclist's head hits a higher area of the windshield at this speed, which has a higher stiffness, which significantly increases HIC. On the other hand, Raslavicius et al use a multibody solver, while this work uses a finite element model that can make specific differences in body deformations in contact during impact [7]. The results obtained are steady with the severity of the literature's injuries by agreeing that this crash scenario generates severe or fatal injuries [8,28].…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…It can be explained due to the different geometry between the fronts of the vehicles used because the cyclist's head hits a higher area of the windshield at this speed, which has a higher stiffness, which significantly increases HIC. On the other hand, Raslavicius et al use a multibody solver, while this work uses a finite element model that can make specific differences in body deformations in contact during impact [7]. The results obtained are steady with the severity of the literature's injuries by agreeing that this crash scenario generates severe or fatal injuries [8,28].…”
Section: Discussionmentioning
confidence: 67%
“…The Pedestrian and Bicycle Crash Analysis Tool (PBCAT) distinguishes around 79 scenarios that consider different factors such as the vehicle's position before the impact, the direction in which one respects the other, and the impact causes [6]. The scenario reported a greater probability of cyclist death, where the motor vehicle is moving in the same direction as the cyclist and the bicycle is reached in the rear side by the front of the car; this scenario is called the overtaking scenario [7,8]. Also, in National Highway Traffic Safety Administration (NHTSA) in the database called Fatality Analysis Reporting System (FARS) from 2008 to 2012, the crash scenario that presented the highest death rate of the cyclist in the United States is the overtaking crash scenario [9], repeating this trend in subsequent years until 2017, which is the last update.…”
Section: Introductionmentioning
confidence: 99%
“…Raslavicius et al 5 studied bicycle–car accidents under four different types of collision and concluded that it is very important to mitigate head and neck impact to the windscreen of the car. If so, a dominant share of fatal cyclist crashes and severe traumatic head injury cases at collision speeds exceeding 40 km/h could be prevented.…”
Section: Introductionmentioning
confidence: 99%
“…When only factors like impact position and vehicle speed are considered in the study, establishing a verified numerical simulation model is a better approach to do the research. [36][37][38] By establishing a verified numerical simulation model, Raslavicˇius et al 39 studied the effects of factors like impact location and direction on injury severity of the bicycler. The aim of this article is to investigate the influences of various factors, most of which are categorical variables, on fatality of the driver.…”
Section: Introductionmentioning
confidence: 99%